Answer:
Step-by-step explanation:
Discussion
You have to rearrange the equation so that y is all by itself on the left and it must be positive. Stay tuned to get the rest of the rule.
x - y = 3 Multiply the whole equation by -1
-1(x - y = 3) Remove the brackets. This gets y to be +
-x + y = - 3 Add x to both sides of the equation.
-x+x + y = -3 + x Combine the left. Notice the x's disappear on the left
y = - 3 + x
Now for the rest of the rule. The number in front of the x is the slope. But, you say, there is no number. Well there is. It's 1.
Answer
The slope of the line is 1.